2019
DOI: 10.3389/ffgc.2019.00076
|View full text |Cite
|
Sign up to set email alerts
|

Edge Effects on Seedling Diversity Are Mediated by Impacts of Fungi and Insects on Seedling Recruitment but Not Survival

Abstract: Growing awareness of the role of enemies in plant community dynamics has led to ecologists exploring how plant-enemy interactions change in human-modified systems. Proximity to forest edges was found to weaken the role of two groups of plant enemies-insect herbivores and fungal pathogens-in increasing plant diversity during the seed-to-seedling transition. However, it is less clear whether edge effects similarly compromise the diversifying effects of fungi and insects on established seedlings. We examined this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Studies using these approaches have demonstrated that natural enemies play an important role in driving tropical tree recruitment and potentially contributing to tropical tree diversity. However, the combined results from these studies also suggest that the overall importance, as well as the relative importance of different enemies (e.g., insects vs. pathogens; Bagchi et al, 2014), varies among sites, among species at the same site, and among life stages (e.g., Fricke et al, 2014;Krishnadas & Comita, 2019). We stress that incorporating such approaches into future studies of CNDD will be key for furthering our understanding of the role of natural enemies in structuring plant communities and maintaining diversity.…”
Section: Effectsmentioning
confidence: 99%
“…Studies using these approaches have demonstrated that natural enemies play an important role in driving tropical tree recruitment and potentially contributing to tropical tree diversity. However, the combined results from these studies also suggest that the overall importance, as well as the relative importance of different enemies (e.g., insects vs. pathogens; Bagchi et al, 2014), varies among sites, among species at the same site, and among life stages (e.g., Fricke et al, 2014;Krishnadas & Comita, 2019). We stress that incorporating such approaches into future studies of CNDD will be key for furthering our understanding of the role of natural enemies in structuring plant communities and maintaining diversity.…”
Section: Effectsmentioning
confidence: 99%
“…However, within‐patch dynamics also influence the composition of communities in fragmented habitats (Haddad et al., 2015; Krishnadas et al., 2018; Ries et al., 2004). Habitat degradation and species loss in fragments often occur because of edge effects—changes to abiotic conditions and biotic interactions near fragment edges (Ibáñez et al., 2014; Krishnadas et al., 2018; Krishnadas & Comita, 2019; Laurance et al., 2006). Ample evidence indicates that edge effects alter ecological communities (Benitez‐Malvido & Martinez‐Ramos, 2003; Krishnadas et al., 2019; Melo et al., 2006; Pfeifer et al., 2017; Ries et al., 2004), but edge effects on the mechanisms that mediate species coexistence remain an underexplored dimension of fragmentation research (Haddad, Gonzalez, et al., 2017).…”
Section: Introductionmentioning
confidence: 99%